Abscisic acid crosstalk with auxin and ethylene in biosynthesis and degradation of inulin‐type fructans in chicory. (22nd May 2021) - Mohammadi, F.; Naghavi, M. R.; Peighambari, S. A.; Khosravi Dehaghi, N.; Khaldari, I.; Bravi, E.; Marconi, O.; Perretti, G.
Abstract: The effect of different hormones on fructan accumulation and the genes regulating biosynthesis and degradation is known; however, information on hormonal interaction mechanisms for fructan content and mean degree of polymerization (mDP) is limited. Cell suspension cultures of chicory were prepared and treated with abscisic acid (ABA), auxin (AUX), ethylene (ETH), ABA + AUX or ABA + ETH, then inulin concentration, mDP of inulin and expression of FAZY genes was determined. A low concentration of AUX and ETH increased fructan content, while a high concentration of AUX and ETH decreased it. Exogenous ABA increased mDP of inulin and this coincided with the low expression of 1‐FEHII . In hormone interactions, ABA changed and adjusted the effect of both AUX and ETH. ABA, together with a low level of AUX and ETH, resulted in a decrease in inulin content and increase in mDP, which coincided with low expression of FEHII . ABA together with a high level of AUX and ETH caused an increase in inulin content with a lower mDP, which coincided with high expression of biosynthesis ( 1‐FFT ) and degradation ( 1‐FEHII ) genes. The effect of both AUX and ETH was almost the same, although the effect of ETH was more severe. ABA had a modulating role in combinations with AUX and ETH. Among biosynthesis and degradation genes, the expression of 1‐FEHII was more affected by these hormones. Abstract : Exogenous hormones counteract each other in the inulin pathway.